Direct comparison transfer of microwave power sensor calibration with an adaptor : modeling and evaluation - Lin, Zhiping (2014)
In this paper, calibration of a microwave power sensor with an adaptor is investigated with direct comparison transfer technique, and mathematically modeled using signal flow-graphs together with non-touching loop rules. The developed calibration model is then implemented practically with a 30 dB attenuator as the adaptor. Its performance is evaluated following the Guide to the Expression of Uncertainty in Measurement and also verified with the Monte Carlo method. Good agreements are observed with all the error |En| ≤ 0.25 over the whole frequency range (up to 18 GHz).